2020
DOI: 10.1088/1555-6611/ab8299
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and hydrostatic pressure effects on the electronic structure, optical properties of spherical segment quantum dot/wetting layer and group velocity of light

Abstract: To investigate hydrostatic pressure and temperature effects on electron energy levels of an InAs spherical segment quantum dot with wetting layer embedded in GaAs barrier, we use the finite element method to solve the Schrödinger equation in the effective mass approximation. Results show that the ground, the first and the second excited state energies decrease (increase) as the hydrostatic pressure (temperature) increases for the constant temperature (pressure). Moreover, given the optical properties of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The advances in nanotechnology have made possible to fabricate different shapes of semiconductor nanosystems such as island, cubic, cylindrical and spherical quantum dots (QDs) by using complex technologies who have used the molecular beam epitaxy (MBE) [1][2][3]. Due to the practical interest of the spherical QD, it is possible to study the hemi-spherical QD thanks to their quantum confinement and physical properties [4][5][6][7]. These immense properties lead to improve the new optical and bionanotechnology devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advances in nanotechnology have made possible to fabricate different shapes of semiconductor nanosystems such as island, cubic, cylindrical and spherical quantum dots (QDs) by using complex technologies who have used the molecular beam epitaxy (MBE) [1][2][3]. Due to the practical interest of the spherical QD, it is possible to study the hemi-spherical QD thanks to their quantum confinement and physical properties [4][5][6][7]. These immense properties lead to improve the new optical and bionanotechnology devices.…”
Section: Introductionmentioning
confidence: 99%
“…The hemi-spherical QD can be described by the confinement potential, the energy spectrum of a single-electron confined and their energy states. In this sense, the electronic structure of hemispherical QD in the presence and absence of donor impurity has been reported [5,6] using the finite element method. They have shown that the dispersions and absorptions are augmenting and exhibit blue-shifts as QD size decreases.…”
Section: Introductionmentioning
confidence: 99%